El método de punto fijo en la medición de la evasión tributaria del Impuesto al Valor Agregado de los comerciantes del mercado Condamine, período 2019 - Gorozabel Palma, Leyda Nataly (2022)
ABSTRACT: Some merchants in the Condamine Market in the city of Riobamba use mechanisms to evade the payment of taxes, among them we find the failure to deliver sales receipts to the final consumer; The Internal Revenue Service of the province of Chimborazo has implemented control mechanisms to eradicate this tax crime, but despite its efforts, high percentages of evasion are currently being handled, this being a difficult phenomenon to combat. This research answers the question, does the tax evasion of the value added tax have a significant on the income of the merchants of the Condamine market?. Aiming to determine through the fixed point method the incidence of the tax evasion of the Value Added Tax on the income of the merchants of the Condamine market during the 2019 period; the hypothetical - deductive method is applied, with a qualitative and quantitative approach. 741 merchants from this market were considered as the study population and a questionnaire was applied to a sample of 192 merchants. The results show that tax evasion depends to a great extent on the income that the merchants had the year prior to the investigation period, leaving aside the elements age, gender, level of education and the place of origin of each of the merchants. From the market. It is concluded that the majority of the merchants of the Condamine Market lack a tax culture since they violate the Law on a daily basis, without being aware that the damage is for society in general. KEY WORDS: Evasion, tax, sales receipts, merchants